Peran Juru Bahasa dalam Seminar Daring tentang Konseling di Era Digital di Masa Pandemi - Wedhowerti, Wedhowerti (Universitas Nusantara PGRI Kediri, 2024)
The Covid-19 Pandemic changed the world pattern and this also impacted adolescent’s psychological state in Indonesia. This very serious adolescent’s psychological problem required prompt and holistic solution. Accordingly, the Department of Guidance and Counseling of Sanata Dharma University Yogyakarta in cooperation with The Chicago School of Professional Psychology took great part in addressing the problem by conducting online international seminar. As an international seminar, this seminar was joined by speakers and participants around the globe with different language background. Therefore, an interpreter was required to bridge the communication among the speakers and participants in the seminar and to eliminate language barrier. A community service program was conducted by interpreting in this seminar. The service program was well conducted that all important topics concerning psychology and guidance and counseling were successfully delivered. All agenda including question and answer sessions and further recommendations were all well conducted.